(untitled) (INFERENCE: Journal of English Language Teaching, 2026)
Reading comprehension remains a complex skill that imposes significant challenges on senior high school students. However, the application of Herringbone technique is deemed to be an effective way to address these challenges. Therefore, this study examines the effect of applying Herringbone technique on senior high school EFL students’ ability to comprehend news item texts as well as analyzes their attitudes towards learning English (reading comprehension of news item texts) using Herringbone technique. Quantitatively, this study employed a quasi-experimental with a pretest-posttest design to assess the effect and students’ learning progress. A pretest was given before treatments, while the posttest was given after the students were taught by applying Herringbone technique. In addition, a 5-point Likert scale questionnaire was also distributed to see the learning attitudes of the students’ in the experimental class. 70 eleventh-grade students from a state senior high school in Pematangsiantar, North Sumatra, were purposefully chosen as the sample in this study. It was revealed that the mean score of the experimental class (78.42) is higher than that of the control class (70.71). The score of the t-test (3.18) is also higher than the t-table (1.99) at a level of significance of 5% of two-tailed test, which means the null hypothesis is rejected and the alternative hypothesis is accepted. The result of the questionnaire also indicates that the students have good and positive attitudes towards learning English (reading comprehension of news item texts) using Herringbone technique. Thus, this study concludes that Herringbone technique could have a significant effect on senior high school students’ ability in comprehending news item texts.